Perspectives on Student Loan Debt Levels: Student Loan Debt Levels and Their Implications for Borrowers, Society, and the Economy - Luke M. Cornelius; Sharon A. Frank (Educational Considerations, 2015)
Upward mobility is a prized aspect of the American dream based upon the belief that those from humble origins can climb the socioeconomic ladder through education and hard work. Increasingly, postsecondary education is an essential component of that dream.
Keywords: student loan; debt levels; implications; economy; borrowers; Society